Address before the Twenty-First Session of the Economic and Social Council of United Nations, New York City - Black, Eugene R. (World Bank, Washington, DC, 2019)
Eugene R. Black, President of the International Bank for Reconstruction and Development, discussed the newest development in the Bank's technical assistance work, including the International Finance Corporation. He explained the significant progress made by Bank in the postwar decade, and the continued and intensified efforts to accelerate the pace of development.